Dampak sosial dan psikologis pada individu yang mengalami konversi agama di Indonesia: Tinjauan teoritis - Fitriati, Bunga; Soleh, Achmad Khudori (Maliki Interdisciplinary Journal, 2023)
Indonesia is a country located in Southeast Asia which is famous for its cultural and religious diversity. Religion has a function that is not only spiritual, but also a human and social function. If an individual is already involved in a religion, then decides to move from his religion with certain factors, this is called Religious Conversion. Even though Indonesia consists of various religions and beliefs, its people live in relatively stable peace and harmony. However, even though Indonesia is a country that embraces many religions, there are still challenges and problems that arise in managing this diversity, one of which is religious conversion. From religious conversions, problems often arise for its adherents, both from a social and even psychological perspective. From the results of the literature study, significant results were obtained regarding social and psychological impacts, especially on interpersonal conflicts. Apart from that, there is also a positive impact on getting new relationships, new experiences, and spiritual improvement to God.